Northern Ireland and European integration: A historical analysis of divergent nationalist discourses - Anne Martin (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
The legacy of colonialism in Northern Ireland has created an ideological divide between Irish nationalism and British unionism through which many questions of political economy are sorted, including questions of conflict, peace and European integration. This paper examines and considers how divergent nationalist discourses surrounding European integration have developed in Northern Ireland throughout history. This divergence can be linked to the fundamentally different and conflicting historical understandings these nationalist projects have of identity, borders and governance.
Keywords: 330; European integration; Northern Ireland; nationalism; borders; discourse